A Young Man With Hereditary Motor And Sensory Neuropathy: A Rare Genetic Association - Quraishi Twinkle , Furial; Rahman, Aminur; Mahmudul hakim, Khondker; Ali Shapnil , Ahammed; Hakim Mishu , Mahbubul (Bangladesh Journal of Medicine, 2024)
Hereditary motor and sensory neuropathies with early onset are uncommon conditions that include Dejerine-Sottas neuropathy, which begins in infancy, and congenital hypomyelinating neuropathy, which manifests in the early postnatal period. However, these two historically defined disease entities are only small parts of the clinical spectrum. It is well recognized that very early onset hereditary neuropathies are frequently caused by de novo dominant mutations in PMP22, MPZ, and EGR2. In addition, mutations in several other dominant and recessive genes for Charcot-Marie-Tooth disease may lead to similar phenotypes. A 20-year-old boy had complaints of weakness of both lower limbs for 1 year, followed by wasting and foot drop, which subsequently involved the upper limbs. Nerve conduction velocity and electromyography of both lower limbs revealed demyelinating sensory motor polyneuropathy. Histological examination of the sural nerve revealed a nerve trunk with perineural soft tissue, with the nerve bundles being irregular and separated by fibrous tissue bands. The later reveals small perivascular infiltration of chronic inflammatory cells, and no granuloma or AFB is seen. The genetic test of whole exome screening for heriditatory neuropathy showed pathogenic (PM2, PVS, PP5) with a gene impact of (NF2: c.363+1G>T), which is a rare entity in our case study to consider the diagnosis despite negative family history. We highlight this rare disease in young man with a high index of clinical suspicion for its diagnosis. Bangladesh J Medicine 2024; 35: 101-105